Validation of a Geant4 model of the X‐ray fluorescence microprobe at the Australian Synchrotron. (13th February 2015) - Dimmock, Matthew Richard; de Jonge, Martin Daly; Howard, Daryl Lloyd; James, Simon Alexander; Kirkham, Robin; Paganin, David Maurice; Paterson, David John; Ruben, Gary; Ryan, Chris Gregory; Brown, Jeremy Michael Cooney
<x xml:space="preserve">Abstract</x> A Geant4 Monte Carlo simulation of the X‐ray fluorescence microprobe (XFM) end‐station at the Australian Synchrotron has been developed. The simulation is required for optimization of the scan configuration and reconstruction algorithms. As part of the simulation process, a Gaussian beam model was developed. Experimental validation of this simulation has tested the efficacy for use of the low‐energy physics models in Geant4 for this synchrotron‐based technique. The observed spectral distributions calculated in the 384 pixel Maia detector, positioned in the standard back‐scatter configuration, were compared with those obtained from experiments performed at three incident X‐ray beam energies: 18.5, 11.0 and 6.8 keV. The reduced χ‐squared (<inline-graphic xlink:href="ark:/27927/pgj4335pk2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) was calculated for the scatter and fluorescence regions of the spectra and demonstrates that the simulations successfully reproduce the scatter distributions. Discrepancies were shown to occur in the multiple‐scatter tail of the Compton continuum. The model was shown to be particularly sensitive to the impurities present in the beryllium window of the Maia detector and their concentrations were optimized to improve the <inline-graphic xlink:href="ark:/27927/pgj4335pk2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> parametrization in the low‐energy fluorescence regions of the spectra.